Chevron-based graphene nanoribbon heterojunctions: Localized effects of lateral extension and structural defects on electronic properties. (August 2018) - Costa, Paulo S.; Teeter, Jacob D.; Enders, Axel; Sinitskii, Alexander
Abstract: Graphene nanoribbon (GNR) heterojunctions have been synthesized by a bottom-up approach on an Au (111) substrate from a mixture of two structurally similar but visually distinct chevron-type molecular precursors. The resulting heterojunctions were composed of the units of chevron GNRs (cGNRs) and new laterally extended chevron GNRs (eGNRs), which contained an additional benzene ring. Because of their intentional visual difference, cGNR and eGNR units could be conveniently distinguished in scanning tunneling microscopy images. Differential conductance (d I /d V ) mapping of GNR heterojunctions revealed differences in electronic structures of cGNRs and eGNRs. Interestingly, the characteristic conduction band states of cGNRs in the d I /d V maps were shown to be sensitive to the effects of both lateral extension of ribbons and the edge defects, emphasizing the importance of synthesizing GNRs and GNR heterojunctions with atomic precision. The d I /d V maps further showed that both effects could be localized within the corresponding GNR units even if they are bonded to structurally and electronically different neighbors, which suggests a possibility of engineering complex GNR-based electronic nanostructures with nanoscale modulation of properties. The new eGNR units could be potentially combined with other chevron-type GNRs, such as nitrogen-doped cGNRs, into a variety of new GNR heterojunctions. Graphical abstract: Image